Functional acellular matrix for tissue repair - Bin Wang; Tang Qinglai; Qian Yang; Mengmeng Li; Shiying Zeng; Xinming Yang; Zian Xiao; Xinying Tong; Lanjie Lei; Shisheng Li (Materials Today Bio, 2023)
In view of their low immunogenicity, biomimetic internal environment, tissue- and organ-like physicochemical properties, and functionalization potential, decellularized extracellular matrix (dECM) materials attract considerable attention and are widely used in tissue engineering. This review describes the composition of extracellular matrices and their role in stem-cell differentiation, discusses the advantages and disadvantages of existing decellularization techniques, and presents methods for the functionalization and characterization of decellularized scaffolds. In addition, we discuss progress in the use of dECMs for cartilage, skin, nerve, and muscle repair and the transplantation or regeneration of different whole organs (e.g., kidneys, liver, uterus, lungs, and heart), summarize the shortcomings of using dECMs for tissue and organ repair after refunctionalization, and examine the corresponding future prospects. Thus, the present review helps to further systematize the application of functionalized dECMs in tissue/organ transplantation and keep researchers up to date on recent progress in dECM usage.